Chronobiology and Metabolism: Is Ketogenic Diet Able to Influence Circadian Rhythm? - Gangitano, Elena; Gnessi, Lucio; Lenzi, Andrea; Ray, David (Frontiers in Neuroscience, 2021)
Circadian rhythms underpin most physiological processes, including energy metabolism. The core circadian clock consists of a transcription-translation negative feedback loop, and is synchronized to light-dark cycles by virtue of light input from the retina, to the central clock in the suprachiasmatic nucleus in the hypothalamus. All cells in the body have circadian oscillators which are entrained to the central clock by neural and humoral signals. In addition to light entrainment of the central clock in the brain, it now emerges that other stimuli can drive circadian clock function in peripheral tissues, the major one being food. This can then drive the liver clock to be misaligned with the central brain clock, a situation of internal misalignment with metabolic disease consequences. Such misalignment is prevalent, with shift workers making up 20% of the working population. The effects of diet composition on the clock are not completely clarified yet. High-fat diet and fasting influence circadian expression of clock genes, inducing phase-advance and phase-delay in animal models. Ketogenic diet is able to induce a metabolic switch from carbohydrate to fatty acid oxidation, miming a fasting state. In recent years, some animal studies have been conducted to investigate the ability of the ketogenic diet to modify circadian gene expression, and demonstrated that the ketogenic diet alters circadian rhythm and induces a rearrangement of metabolic gene expression. These findings may lead to new approaches to obesity and metabolic pathologies treatment.